Inovasi Pembelajaran sebagai Strategi Penguatan Literasi Kritis Peserta Didik - Wenni Septia Pratiwi; Indah Ratu Sehati; Alhafiz Rasya Ramadhan; Sani Safitri; Rani Oktapiani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This article discusses innovation in the learning process as an important strategic step to improve the quality of education, especially in developing students' critical literacy skills. Critical literacy is an essential skill for students to face the complexity of information and technology in the 21st century. This paper aims to explore the role of learning innovation as a strategy to strengthen critical literacy. This research uses a qualitative approach through literature study, by reviewing various scientific references related to learning innovation, critical literacy, 21st-century learning principles, and the role of teachers in the learning process. The results of the study indicate that learning innovation designed in a contextual, collaborative, and student-focused manner can improve their ability to understand, analyze, evaluate, and reflect on information critically. In addition, the role of teachers as facilitators, motivators, and agents of innovation has proven crucial in creating effective and meaningful learning experiences. Learning innovation can be an effective strategy to strengthen students' critical literacy while preparing them to face the challenges of the digital era and modern society.